The reality of the employment of distance education due to corona disease in private Kuwaiti schools – A Field Study on the Principals of private Kuwaiti schools – - Al-Rasheedi, Fawaz Dheem (Journal of Educational and Psychological Sciences, 2021)
The aim of the study was to identify the reality of the employment of distance education due to corona disease in private Kuwaiti schools from the principals perspective. To achieve this study, the descriptive approach was used، where a questionnaire was developed, consisting of three areas (knowledge، skills، and evaluation) with 20 paragraphs, and its validity and stability was verified, and then it was distributed on the sample of the study which was consisted of (140) principals.The result of the study showed the reality of the employment of the distance education due to corona disease in the private Kuwaiti schools from the principals perspective, was middle and with an average arithmetic (2.49). The results also showed significant differences in the evaluations of the study’s sample members for The reality of the employment of the distance education due to corona disease from the principals perspective according to the gender variable in favor of females, and no significant differences in the evaluations of the study’s sample members for The reality of the employment of the distance education due to corona disease from the principals perspective according to the School stage.In light of the results, the researcher recommended that the Ministry of Education should hold more courses and training workshops specialized in the field of distance education in the educational process for teachers and administrators، developing and training students in modern technology skills.
Keywords: distance education; corona disease